2004
DOI: 10.1002/14651858.cd000353.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Homeopathy for chronic asthma

Abstract: Characteristics of included studies [ordered by study ID] Methods Design: parallel group Allocation concealment: by numbered pharmacy Blinding: patients and evaluators Drop-outs/withdrawals: 7/10 in Blatta and placebo groups respectively Jadad score: 1-2-1 Study schedule: six months. Participants N = 69 (34 male, 35 female). Age range: 1-12 years. Diagnosis: Asthma (?). Inclusion criteria: "at least 3 bronchospastic episodes with intervals of 3 months or less, or continuous wheeze for at least 3 months". Setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(48 citation statements)
references
References 15 publications
0
41
0
6
Order By: Relevance
“…Its authors concluded that 'there is not enough evidence to reliably assess the possible role of homeopathy in asthma'. 18 No data from controlled clinical trials seem to exist for eczema. 19 In the case of infections, a Cochrane review is available of homeopathic oscillococcinum for preventing and treating influenza and influenza-like syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…Its authors concluded that 'there is not enough evidence to reliably assess the possible role of homeopathy in asthma'. 18 No data from controlled clinical trials seem to exist for eczema. 19 In the case of infections, a Cochrane review is available of homeopathic oscillococcinum for preventing and treating influenza and influenza-like syndromes.…”
Section: Discussionmentioning
confidence: 99%
“…To make a convincing case, a large, unbiased systematic review is needed. The Cochrane Collaboration has already done this for several conditions, [6][7][8][9][10] but has yet to find compelling evidence of any benefit. Usually, few or no well-conducted trials exist.…”
Section: -5mentioning
confidence: 99%
“…Isopathy, also popularly known as “homeopathic immunotherapy” (HIT), is the use of homeopathic dilutions from the causative agent of the disease itself (e.g., organisms or allergens), or from a product of the disease process, to treat the condition, strategically different from individualized homeopathic prescribing in the classic sense. However, a Cochrane systematic review [8] in the previous decade concluded that there was not enough evidence to reliably assess the possible role of homeopathy in asthma because of heterogeneity in the type of homeopathy and study designs; and until stronger evidence existed, no further recommendations could be made about homeopathic treatment. Since publication of this paper, no further systematic review has been undertaken in the concerned subject.…”
Section: Introductionmentioning
confidence: 99%